The effects of silver nitrate on Mycobacterium abscessus biofilms in a simulated antimicrobial showerhead environment - Sarah Pitell; Cheolwoon Woo; Jill Millstone; Jill Millstone; Jill Millstone; Janet Stout; Janet Stout; Leanne Gilbertson; Sarah-Jane Haig; Sarah-Jane Haig (Frontiers in Public Health)
Antimicrobial silver materials for drinking water disinfection have become increasingly popular in building-wide systems (e.g., copper-silver ionization) and point-of-use applications (e.g., silver containing plumbing fixtures) to combat the microbial growth of drinking water associated pathogens that can cause infections in the immunocompromised (DWPIs). However, evaluations of various silver-containing treatments suggest that their efficacy is often temporary or incomplete. A potential explanation of these observations is insufficient dosing of silver into the drinking water to reduce these types of microorganisms, which are known to be more resistant to biocides. Instead, sublethal exposure may cause these microorganisms to adapt in ways that increase their resistance to disinfection. In this study, we assessed the effects of different silver concentrations on biofilms of clinically and environmentally isolated Mycobacterium abscessus, a biofilm-forming member of the drinking water microbiota with public health and environmental significance, in a bench-scale system operated to simulated the use patterns of antimicrobial showerheads. We found that high concentrations of silver significantly reduced biofilms cell densities and impacted cellular aggregation behavior, but ultimately made the resulting treated water non-potable due to the concentration of silver needed to solicit these effects. Silver concentrations that were more appropriate for drinking water applications resulting in limited reduction in viable M. abscessus. Additionally, transcriptomic analysis revealed that genes related to stress survival were upregulated in all experimental conditions: genes related to flavoprotein, chaperone, and protease synthesis, ribosome synthesis, and cysteine and methionine metabolism were upregulated in the lower dose condition, and peptidoglycan synthesis and antioxidant production were upregulated in the higher silver dose condition. These expressional changes may enhance survival and pathogenicity traits in M. abscessus after silver exposure. Overall, our findings indicate that silver exposure drives meaningful changes in biofilm behavior and gene expression in M. abscessus isolates, yet does not inactivate M. abscessus under the simulated conditions.